Essential Oils from Argentinean Aromatic Plants - Juliani, Hector Rodolfo (2004)
A research association was established between Rutgers University, USA and Argentinian Universities, National University of La Rioja and National University of Córdoba, to identify aromatic and medicinal plants of potential commercial interest for future cultivation and conservation programs. This study was part of a larger project to study the uses of native aromatic plants in commercial products in Argentina and to evaluate the content and composition of essential oils in some of the species growing wild in the Los Llanos region (La Rioja Province, midwestern Argentina). A regional market survey showed that the majority of these species are utilized commercially to prepare a wide range of commercial herbal products that include non-prescription drugs, composite yerba mate, herbal teas and non-alcoholic beverages. Lippia turbinata, locally known, as "Poleo" was the most used aromatic plant in Argentina, being found in the 38 % of commercial products, whereas, L. integrifolia (“incayuyo”) was present in 23 % of products. Chenopodium ambrosioides (“paico”) and Aloysia polystachia (“Te del burro”) were found in 5 % and A. gratissima (“Palo amarillo”) in only 1 % of commercial herbal products. The essential oil of these species and other aromatic plants from Los Llanos region (La Rioja Province) were evaluated. We found that several of the aromatic plants from this region of Argentina could serve as potential new sources of essential oils. In addition, the volatile oils of Lippia salsa and Larrea divaricata are described for the first time.